Diseño de un plan de negocio para un Food Truck de desayunos y almuerzos en la via Cali Yumbo (2024)
The purpose of the project is to formulate a business plan for a Food Truck on the Cali Yumbo road (industrial sector), for which it was proposed to design a business plan model to know the conditions of the existing market and its respective variations. , which is recognized for its different characteristics such as the presentation of the dishes offered with unique recipes at affordable prices to generate an impact on permanent or mobile Caleños and Yumbeños customers who travel through the area, making them loyal and preferring us